Alkaline phosphatase predicts short-term postoperative outcome in adult patients with moyamoya disease - Sun, Wei; Wang, Huihui; He, Qiheng; Li, Junsheng; Liu, Chenglong; Zheng, Zhiyao; Mou, Siqi; Zhang, Bojian; Zhao, Zhikang; Tao, Chuming; Liu, Wei; Shi, Xiangjun; et al. (Frontiers in Neurology, 2025)
BackgroundAlkaline phosphatase (ALP) has played a pivotal role in vascular diseases in recent years. However, the association between ALP level and postoperative complications of moyamoya disease (MMD) has not been studied.Patients and methodsBlood samples were collected from recruited patients with MMD. The serum ALP concentrations of the patients were determined using non-frozen specimens via an automated enzymatic assay. Patients were then divided into two groups according to the median, and a comparative analysis was performed. Patients were stratified into two cohorts for statistical evaluation based on the occurrence of postoperative stroke events. We employed a nomogram to identify risk factors for postoperative events. We also created a Cox model to analyze the risk factors for postoperative stroke events, including ALP. Furthermore, we plotted a restricted cubic spline (RCS) of ALP concentration vs. postoperative stroke events.ResultsWe could find that the ALP concentration of non-postoperative stroke group and postoperative stroke group was 68.70 U/L and 71.15 U/L. This nomogram showed that ALP was a risk factor for postoperative events, and the Hosmer–Lemeshow goodness-of-fit test was employed, suggesting that the model was reliable (χ2 = 8.507, p = 0.386). And it also could obverse that there was a statistically positive correlation from the RCS between ALP concentration and postoperative stroke events Cox analysis (HR = 1.006, 95% CI = 1.002–1.010, p = 0.008).ConclusionsALP levels may predict the short-term postoperative outcomes of MMD patients undergoing surgical treatment.